Surface-flow constructed wetlands dominated by Cladophora for reclaiming nutrients in diffuse domestic effluent. (March 2018) - Zhu, Huaqing; Lu, Xiwu; Dai, Hongliang
Abstract: In this work, a surface-flow constructed wetland (SFCW) dominated by Cladophora was used to remove and reclaim nutrients in diffuse domestic effluent (DDE) discharged from rural regions around Taihu Lake, a eutrophic shallow lake in China. Growth rate of Cladophora was investigated and linked to ambient factors and nutrient consuming rates. The growth performances of Cladophora and animal-feed microbes were studied during the commissioning of SFCW. Results show that the growth rate of Cladophora was closely correlated with field temperature and surface irradiance, while surface coverage was suitable for the manipulation of SFCW. Harvest of Cladophora along with animal-feed microbes and removal of nutrients in DDE could be achieved by manipulating surface coverage to drag growth rate back at the end of linear zone and to quickly restore Cladophora biomass in the mid zone of surface growth rate. Among four stages of the commissioning, concentrating stage experienced the majority species of animal-feed microbes and maximal nutrient removal; during decomposing stage, however, the reproduction of animal-feed microbes and nutrient removal were lower, whereas the density of pathogens was higher. Graphical abstract: Highlights: A surface-flow constructed wetland (SFCW) dominated by Cladophora was developed. Cladophora growth was correlated with field temperature and surface irradiance. Nutrient removal and harvest of Cladophora and microbes were achieved simultaneous.